Mediasi Return On Asset Terhadap Harga Saham dengan Pengaruh Current Ratio dan Modal Kerja pada Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia - Akbar, Ali (Ekonomis: Journal of Economics and Business, 2024)
The aim of the research is to know and analyze the return on asset as a mediator of the effect of current ratio and working capital on stock price at pharmaceutical sub-sector companies on the Indonesian stock exchange. That research is using secondary data from the annual financial statements. The purposive sampling method was used with six companies that were sampled as pharmaceutical sub-sector companies in the Indonesian stock exchange period of 2018–2022. Data analysis in this research uses path analysis with SPSS software. The resulting research informs : 1) current ratio and working capital positive simultaneously have significant effect on Return On Asset, 2) current ratio has positive and significant effect on Return On Asset, 3) working capital has negative and significant effect on Return On Asset, 4) current ratio and working capital positive simultaneously have significant effect on stocks price, 5) current ratio has positive and significant effect on stocks price, 6) working capital has negative and no significant effect on stocks price, 7) Return On Asset has positive and significant effect on stocks price and 8) indirectly current ratio and working capital through return on asset does not have a significant influence effect on stocks price.